Honda Tiger 2000 Bike Engine Modification Test against Exhaust Emissions and Fuel Consumption - Bahtiar, Bahtiar Wilantara; Hamid Nasrullah; Atip Suwarno; Ahmad Nurkholis; R Chandra; Tombak Rizky Wijaya; Firman Handoko (Politeknik Dharma Patria Kebumen, 2021)
This study aims to determine the effect of modification of the Honda Tiger 2000 on exhaust emissions of CO and HC. The method used is to modify the carburettor venturi piston and replace the rocker arm with a roller rocker arm. The exhaust emission test used a gas analyzer type SUKYOUNG SY-GA 401. The object of the study was a Honda Tiger 2000 motorcycle. The results showed that modification of the Honda Tiger 2000 motorcycle at idle, 1000 rpm, 1500 rpm, and 2000 rpm increased CO emissions but reduced HC emissions. Based on comparing the motorcycle emission threshold values for manufacture â‰¤ 2010, namely CO emissions exceeding 5.5% and HC emissions less than 2400 ppm. Pertamax Turbo fuel consumption is more efficient than Pertalite with a distance ratio of 45 km requiring 1L Pertamax Turbo and 1.4L Petalite.